Effects of tranexamic acid on human nasal ciliary beat frequency - Behr, W. (Eur Arch Otorhinolaryngol, 2021)
BACKGROUND: Patients with recurrent epistaxis, particularly due to hereditary hemorrhagic telangiectasia (HHT) are recommended to apply topical tranexamic acid (TXA) to reduce bleeding events. Those patients may suffer ciliary dysfunction due to TXA’s effects on ciliary beating frequency (CBF) and their consequences. METHODOLOGY/PRINCIPAL: Human nasal epithelial cells were harvested with a nasal brush in 30 healthy subjects. We investigated the CBF in RPMI medium using high-frequency video microscopy. TXA was added to the cells in various concentrations ranging from 2 to 5%, including the therapeutic concentration (2%) and a control (0%). RESULTS: CBF in the control condition was 6.1 ± 1.6 Hz. TXA reduces CBF in a time and concentration dependent manner, to, e.g. 4.3 ± 1.2 Hz with 2% TXA and 3.3 ± 0.9 Hz with 5% TXA after 16–20 min. The differences in CBF were statistically significant for all concentrations of TXA. CONCLUSIONS: TXA has the potential to significantly impair nasal epithelial function. Therefore, frequent or regular topical nasal application of TXA should be done under close monitoring of nasal function, especially in patients with co-morbidities like chronic rhinosinusitis.